Creatine supplementation does not impare the thermoregulatory response during a bout of exercise in the heat - Weiss, B. A.; Powers, M. E. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The aim of this work was to examine the effects of creatine (Cr) supplementation on resting body water volumes and on core temperature and sweat loss during a bout of exercise in a warm environment. Methods: Twenty-four aerobically trained male subjects (age 22.93±3.01 years, height 179.52±7.28 cm, mass 82.06±14.32 kg) volunteered to participate in this study. Each subject was assessed for resting body water volumes and for body mass (BM), heart rate (HR), blood pressure (BP), and core temperature immediately before and following a 60-min bout of exercise in a warm environment. Core temperature, HR, and BP were also recorded at 10-min intervals during exercise. Subjects were then randomly assigned to either a Cr or placebo (P) group. Each subject returned following a 5-day supplementation period and was reassessed using identical testing procedures. BM was measured using a standard electronic scale. Body water volumes were assessed using a multi-frequency BIS (Xitron Technologies, San Diego, CA, USA). Core body temperature was measured using a CorTemp Disposable Temperature Sensor and a CT2000 Miniaturized Ambulatory Recorder (HTI Technologies, Inc., Palmetto, FL, USA). Results: The Cr group experienced a significant increase in all body water volumes. No changes were observed in the P group. No changes in core temperature or sweat loss were observed in either group following supplementation. Conclusions: Cr loading did not impair the thermoregulatory response during a bout of exercise in the heat.